VD_FINDINFO ML / 2010 / 183 vom 15. April 2010 - VD Tribunal cantonal (2010)
MAINLEVÉE DÉFINITIVE, BAIL À LOYER, COMPENSATION DE CRÉANCES, TITRE EXÉCUTOIRE | 120 CO, 124 al. 2 CO, 80 LP, 81 LP, 103 LTF